2017
DOI: 10.1111/j.1600-0390.2017.12178.x
|View full text |Cite
|
Sign up to set email alerts
|

Memory, Landscape & Mortuary Practice

Abstract: Stone Age people handled their dead in various ways. From the Late Mesolithic period onwards, the deceased were also buried in formal cemeteries, and according to radiocarbon dates, the cemeteries were used for long periods and occasionally reused after a hiatus of several hundred years. The tradition of continuous burials indicates that the cemeteries were not only static containers of the dead but also important places for Stone Age communities, which were often established in potent places and marked by lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…At Jönsas, a total of 27 burials span from the Late Mesolithic (sixth–seventh millennium BC) to the early third millennium BC (e.g. Ahola 2017); excavations at Vaateranta have identified up to 22 burials from the fourth millennium BC (Katiskoski 2004). The interpretation of both sites as cemeteries rests principally on pit morphology and the shapes of red ochre deposits, as well as the human dental remains from eight burials at Vaateranta (Katiskoski 2004; Ahola et al .…”
Section: Assessing the Burial Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…At Jönsas, a total of 27 burials span from the Late Mesolithic (sixth–seventh millennium BC) to the early third millennium BC (e.g. Ahola 2017); excavations at Vaateranta have identified up to 22 burials from the fourth millennium BC (Katiskoski 2004). The interpretation of both sites as cemeteries rests principally on pit morphology and the shapes of red ochre deposits, as well as the human dental remains from eight burials at Vaateranta (Katiskoski 2004; Ahola et al .…”
Section: Assessing the Burial Hypothesismentioning
confidence: 99%
“…The interpretation of both sites as cemeteries rests principally on pit morphology and the shapes of red ochre deposits, as well as the human dental remains from eight burials at Vaateranta (Katiskoski 2004; Ahola et al . 2016).…”
Section: Assessing the Burial Hypothesismentioning
confidence: 99%
“…15-16). Even in European prehistory, important burial sites have often been either continuously in use for millennia or were reused after a considerable hiatus of several hundred years (e.g., Wessman 2010, Williams 2013, Ahola 2017b. For example, the people connected with the Yamnaya in south-eastern Europe occasionally made new internments in their burial mounds (Heyd 2011).…”
Section: Negotiating With the Supernatural To Create A Sense Of Belongingmentioning
confidence: 99%
“…Interestingly, recent studies have shown that groups connected with the CWC also reused older burial monuments with new burials (e.g., Holtorf 1998, Malmer 2002, Ebbesen 2008, Bourgeois 2013, Jeunesse 2014, Tunia and Włodarczak et al 2016, Ahola 2017b, Malmström et al 2019. Although some of the reused burial sites have been identified as previous CWC graves (e.g., Tunia and Włodarczak 2016, p. 224), considerably older monuments were also chosen as burial locations.…”
Section: Negotiating With the Supernatural To Create A Sense Of Belongingmentioning
confidence: 99%
See 1 more Smart Citation